Iron status of young children from immigrant families. Issue 12 (31st August 2016) - Saunders, Natasha Ruth; Parkin, Patricia C; Birken, Catherine S; Maguire, Jonathon L; Borkhoff, Cornelia M
Abstract : Objectives: Children from immigrant families may be at risk for iron deficiency (ID) due to differences in pre-migration and post-migration exposures. Our objectives were to determine whether there is an association between family immigrant status and iron stores and to evaluate whether known dietary, environmental or biological determinants of low iron status influence this relationship. Design: This was a cross-sectional study of healthy urban preschool children (12–72 months) recruited from seven primary care practices in Toronto. Laboratory assessment of serum ferritin and haemoglobin and standardised parent-completed surveys were completed between 2008 and 2013 during routine health maintenance visits. Multiple regression analyses were used to evaluate the association between family immigrant status and serum ferritin, ID (ferritin <14 μg/L) and iron deficiency anaemia (IDA) (ferritin <14 μg/L and haemoglobin ≤110 g/L). Results: Of 2614 children included in the analysis, 47.6% had immigrant family status. The median serum ferritin was 30 μg/L and 10.4% of all children had ID and 1.9% had IDA. After adjusting for maternal ethnicity and education, age, sex, income quintile, cow's milk intake, breastfeeding duration and bottle use, there were no significant associations between immigrant status and ferritin, ID or IDA. Significant predictors of low iron status included age, sex, cow's milk intake and breastfeeding duration. Conclusions: We found no association between family immigrant status and iron status after including clinically important covariates in the models. These data suggest immigrant children may not need enhanced screening for iron status or targeted interventions for iron supplementation.